1996
DOI: 10.1177/00957984960224002
|View full text |Cite
|
Sign up to set email alerts
|

Further Examination of the Spirituality Scale

Abstract: This study provides additional data on a newly developed paper-and-pencil measure of spirituality from an Afrocultural perspective. Sixty-eight African American and 75 European American college students completed the Spirituality Scale and indices of internal, external, and quest religious motivation, divine and personal agency, and religious and existential well-being. Results indicated that the Spirituality Scale had good internal consistency in both cultural groups and that the level of endorsement of femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 15 publications
1
71
0
Order By: Relevance
“…The analysis began with exploring the domains of the SWBS, a popular scale known for its reliability and validity but also questioned for its fit with minority groups [49]. The scale was confirmed as a two-factor solution scale with this pilot sample and CFA results supported the psychometric properties of the SWBS.…”
Section: Discussion Implications and Conclusionmentioning
confidence: 74%
See 1 more Smart Citation
“…The analysis began with exploring the domains of the SWBS, a popular scale known for its reliability and validity but also questioned for its fit with minority groups [49]. The scale was confirmed as a two-factor solution scale with this pilot sample and CFA results supported the psychometric properties of the SWBS.…”
Section: Discussion Implications and Conclusionmentioning
confidence: 74%
“…The domains of the SWBS that include the RWB or Religious Well Being dimension that examines a vertical relationship or an individual's relationship with the Christian God; and the horizontal relationship or Existential Well Being (EWB) dimension help explain the connection between an individual and others as well as general satisfaction and meaning in life [29]. Previous studies conducted with African American samples found that the structure of the SWBS did not adequately measure subjective well-being in regards to a spiritual domain of human functioning and called into question the validity of the scale among African Americans [49] and determined that a five-factor rather than a two-factor solution was an appropriate measure of spiritual wellbeing among this population [51].…”
Section: Discussion Implications and Conclusionmentioning
confidence: 99%
“…Many African Americans have been reared with spiritual convictions and a belief in God or a higher power. Research on Black inner-city youth suggests that young people who place a greater emphasis on spirituality report fewer problem behaviors, lower levels of delinquency, and more favorable social outcomes (Jagers & Mock, 1993;Jagers & Smith, 1996). In this case study, Celi's spiritual beliefs and religious community provided social support and belonging.…”
Section: Clinical Issues and Summarymentioning
confidence: 79%
“…Spirituality Scale Jagers, Boykin, and Smith (see Jagers and Smith 1996) developed the Spirituality Scale to measure spirituality from an African American cultural perspective. The scale is based on initial work by Jagers and Mock (1993) who developed the Afro-Cultural Orientation Questionnaire that included spirituality as one of the three concepts, along with communalism and affect, it measured.…”
Section: Orientation Toward Religion and Spirituality Indexmentioning
confidence: 99%